Negative charge at aspartate 151 is important for human lens αA-crystallin stability and chaperone function. (May 2019) - Takata, Takumi; Matsubara, Toshiya; Nakamura-Hirota, Tooru; Fujii, Noriko
Abstract: Aggregation of lens protein is a major cause of senile cataract. Lens crystallins contain many kinds of modification that accumulate over lifespan. In particular, isomerization of Asp 151 in αA-crystallin has been found in aged lenses; however, its significance is unknown. The purpose of this study was to determine the effects of isomerization of Asp 151 in αA-crystallin. Trypsin digestion followed by liquid chromatography–mass spectrometry analysis of the water-soluble high molecular weight (HMW) fraction from human lens samples showed that isomerization of Asp 151 in αA-crystallin is age-independent, and that 50% of isomerization occurs shortly after birth. However, the extent of Asp 151 isomerization varied with the size of αA-crystallin oligomer species separated from the HMW fraction from aged lens. To evaluate the effects of modification, Asp 151 of αA-crystallin was replaced by glycine, alanine, isoleucine, asparagine, glutamate, or lysine by site-directed mutagenesis. All substitutions except for glutamate decreased heat stability and chaperone function as compared with wild-type αA-crystallin. In particular, abnormal hydrophobicity and alteration of the charge state at Asp 151 caused loss of stability and chaperone activity of αA-crystallin; these properties were recovered to some extent when the mutant protein was mixed 1:1 with wild-type αA-crystallin. The results suggest that, by itself, age-independent isomerization of Asp 151 in αA-crystallin may not contribute to cataract formation. However, the long-term deleterious effect of Asp 151 isomerization on the structure and function of αA-crystallin might cooperatively contribute to the loss of transparency of aged human lens.